Intra‐abdominal infections among adult intestinal and multivisceral transplant recipients in the 2‐year post‐operative period. Issue 1 (13th December 2019) - Spence, Amanda Blair; Natarajan, Madhuri; Fogleman, Sarah; Biswas, Roshni; Girlanda, Raffaele; Timpone, Joseph
Abstract: Background: Intestinal and multivisceral transplantations are treatment options for patients with intestinal failure. Transplantation is often complicated by abdominal and/or bloodstream infections in the post‐operative period. Methods: A retrospective chart review of all adults who underwent intestinal or multivisceral transplantation at our institution from 2003 to 2015 was performed. Data were collected for 2 years post transplant. Results: A total of 106 intestinal or multivisceral transplants were performed in 103 patients. The median age at the time of transplant was 44 (IQR: 34‐52) with 55% (n = 58) male and 45% (n = 48) female. There were 46 (43%) intra‐abdominal infections post transplant among the 103 patients, and six transplant recipients (13%) developed concurrent bloodstream infections. The median time to first intra‐abdominal infection was 23 days (IQR: 10‐48). For those with organisms isolated in culture, forty‐seven percent of the isolates were gram negative, 39% gram positive, 7% anaerobes, and 7% yeast. The most common isolates were enterococci at 28%, E. coli at 14%, and Klebsiella spp at 13%. Sixty‐three percent of the enterococci were vancomycin‐resistant enterococci (VRE), and 22% of the gram‐negative isolates were extended spectrum beta‐lactamases (ESBLs). Patients with intra‐abdominal infections had longer hospital post‐transplant length of stays at a median of 35 days (IQR: 25‐48) vs 23 days (IQR: 17‐33) for those without infections, P = .0012. There was no difference in all‐cause mortality in patients with or without intra‐abdominal infections, P = .654. Conclusions: Intra‐abdominal infections are common in intestinal or multivisceral transplant recipients, but despite this complication, we found no increased risk of mortality. These transplant recipients are also at risk for infection with drug‐resistant organisms.